E-learning and Artificial Intelligence: A Solution to the Limitations of Educational Infrastructure in Afghanistan - Mir Mohammad Naim Sadat (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Higher education in Afghanistan faces chronic challenges stemming from decades of conflict, political instability, and underinvestment. Universities operate with limited infrastructure, outdated curricula, and overcrowded classrooms, leaving students underprepared for the demands of a competitive global labor market. The COVID-19 pandemic further exposed the fragility of the sector, as efforts to shift toward online learning were hindered by poor connectivity, unreliable electricity, and insufficient institutional readiness. This study investigates the potential of e-learning combined with artificial intelligence (AI) to address these systemic limitations and to provide a sustainable pathway for educational reform in fragile contexts. Adopting a qualitative design, the study draws on documentation analysis, field observations, and semi-structured interviews with lecturers, administrators, and students in Afghan universities. The data were analyzed thematically, focusing on infrastructure barriers, institutional capacity, and perceptions of AI-enhanced e-learning. Findings highlight that while conventional e-learning platforms expanded access during emergencies, they often lacked adaptability, personalization, and effectiveness in sustaining engagement. Participants demonstrated limited technical literacy regarding AI but expressed strong interest in its potential to improve teaching efficiency, student support, and inclusiveness. The absence of coherent policy frameworks and persistent gender and geographic inequalities emerged as critical challenges to equitable implementation. This study contributes to the state-of-the-art by extending discussions of AI in education into a fragile-state context, where assumptions of stable infrastructure and governance do not apply. It also problematizes the universality of technology adoption theories, suggesting the need for adaptations that incorporate structural and socio-cultural variables. AI-enabled e-learning can partially mitigate Afghanistan's educational infrastructure deficits when implemented alongside capacity building, inclusive design, and supportive governance frameworks. These findings hold relevance not only for Afghanistan but also for other fragile states seeking innovative, equitable, and sustainable educational solutions.